ВІДНОВЛЕННЯ ДИНАМІЧНИХ СПОТВОРЕНЬ ВИХІДНОГО КАНАЛУ, ПЕРЕДАЧЕЮ БЕЗПЕРЕРВНИХ СИГНАЛІВ - Ivanyuk, Vitaliy Anatolievich; Halmuhamedova, Feruza Arslanbekovna (Kamianets-Podilskyi National Ivan Ohiienko University, 2012)
Signal restoring algorithms, subjected to essential dynamic distortions in channels transmitting continuous signals in conditions of noise availability are considered in this paper. It is shown, that the application of developed algorithms digital filtration made possible to avoid unstable operation of operator inversion of the channel. For maintenance stability of the delivered problem solution with the purpose of maximum use additional a priory information on required signal and noise regularization methods of ill posed problems are used. Some results of computer experiments are shown.